Pengaruh Organizational Citizenship Behavior (OCB) dan Determinan Kompensasi Terhadap Kinerja Karyawan Samsat Krian - Auly Fadilah Permata Sari; Afifatus Sholikhah; Chintiya Wulandari; Ucyk Nurul Farida; Ninik Fauziyah; Putri Yunisya Cherlina Pratama (Universitas 45 Surabaya, 2024)
In an era that continues to grow, competition in the business world is increasing rapidly, rapid development and preparation for the global economy encourage workers to be more competitive. This research aims to examine the effect of independent variables, namely Organizational Citizenship Behavior (OCB) and Compensation Determinants on the dependent variable, namely Employee Performance. This study uses a quantitative approach, data collection is done by distributing questionnaires to employees of the Krian samsat. The sample in this study amounted to 50 employees. Data analysis in the study was processed using the help of Partial Least Square (PLS) version 4.0. The results showed that organizational citizenship bahavior has a positive but insignificant effect on the performance of Krian samsat employees and compensation determinants have a positive and significant effect on the performance of Krian samsat employees